Immune suppression of vaccine-induced CD8+ T-cell responses by gamma retrovirus envelope is mediated by interleukin-10-producing CD4+ T cells - Podschwadt, Philip; Malyshkina, Anna; Windmann, Sonja; Papadamakis, Athanasios; Kerkmann, Leonie; Lapuente, Dennis; Tenbusch, Matthias; Lu, Mengji; Schindler, Michael; Lang, Karl Sebastian; Hansen, Wiebke; Bayer, Wibke (Frontiers in Immunology, 2022)
Retroviral envelope (Env) proteins have long been recognized to exhibit immunosuppressive properties, which affect the CD8+ T cell response to an infection but also to immunization. Interestingly, we could show before in the Friend murine leukemia virus (F-MuLV) model that also the surface Env protein gp70 plays a role in immunosuppression, in addition to the immunosuppressive function attributed to the transmembrane Env protein. We now demonstrate that the immunization with F-MuLV Env leads to a significant increase in interleukin-10 (IL-10) producing CD4+ T cells, and that the induction of CD8+ T cell responses in the presence of Env is rescued if the capacity of CD4+ T cells to produce IL-10 is abrogated, indicating a mechanistic role of IL-10-producing CD4+ T cells in mediating the Env-induced suppression of CD8+ T cell responses in Env co-immunization. We found that CD8+ T cell responses against different immunogens are not all equally affected. On the other hand, suppression of immunity was not only observed in co-immunization experiments but also for immune control of subcutaneous tumor growth after an Env immunization. Finally, we show that suppression of CD8+ T cells by the surface Env protein is not only observed for Friend MuLV Env but also for the Env proteins of other gamma retroviruses. Taken together, our results show that IL-10-producing CD4+ T cells are mechanistically underlying the Env-mediated suppression of CD8+ T cell responses and suggest the presence of an immunosuppressive motif in the surface Env protein of gamma retroviruses.